A Strength-Based Support Group for International College Students: A Pilot Study. Issue 1 (2nd January 2022) - Prasath, Priscilla Rose; Lim, Alex Lian Sheng; Steen, Sam
ABSTRACT: The United States remains the top host of international college students globally. Within the counseling literature, international college students' acculturative experiences and characteristics are often studied through the lens of the medical model. This gap lends itself to opportunities for a paradigm shift in group counseling practice to foster their wellbeing, by building on their existing psychological capabilities such as hope, efficacy, resiliency, and optimism, referred to as Psychological Capital (PsyCap). The purpose of this practice article is to showcase the development, implementation, participants' feedback, pilot evaluation, and implications of an eight-week strength-based support group called the International SuperHERO.